Seeking accountability for Nazi and war crimes in East and Central Europe: a people's justice? - Voisin, Vanessa (Rochester Studies in East and Central Europe, 2022)
The thirst for post-World War II justice transcended the Cold War and mobilized diverse social groups. This is a story of their multilayered and at times conflictual interactions